Lower leg anterior and lateral intracompartmental pressure changes before and after classic versus skate nordic rollerskiing in collegiate nordic skiers - Woods, K. M.; Schultz, B. B.; Petron, D. J.; Hayes, B. T.; Hicks-Little, C. A. (Journal of Athletic Training, 2012)
Context: Increasing awareness of chronic exertional compartment syndrome (CECS) among Nordic skiers warrants the need for specific analysis of intracompartmental pressures (ICPs) before and after Nordic skiing. Objective: The purpose of this study was to determine if lower leg anterior and lateral ICPs are increased after a 20-minute Nordic rollerskiing time-trial, and to determine if a difference exists between post exercise ICPs for classic versus skate rollerskiing. Design: Mixed Factorial Repeated-Measures Design. Setting: Outdoor, paved exercise loop. Patients or Other Participants: Seven collegiate Nordic skiers with no history of knee, lower leg, or ankle surgery participated in the study (3 men, 4 women; age = 22.71 ± 1.38 yrs, height = 175.36 ± 6.33 cm, mass = 71.71 ± 6.58 kg). All partici-pants averaged 500-600 training hours per year, were registered with the International Ski Federation (FIS), had trained using both the classic Nordic skiing technique and skate Nordic skiing technique for at least the past 12 months, and had trained in the United States for at least 85% of the time over the past 12 months. Interventions: Independent variables were Nordic ski technique (classic and skate), gender (male or female), and time (pre exercise, 1-minute postexercise, and 5-minutes postexercise). Main Outcome Measures: Anterior and lateral compartment ICPs (mmHg), and lower leg pain were measured. Results: Results showed an increase in ICPs for all participants for both anterior and lateral compartments (p = 0.000 and p= 0.002, respectively), regardless of technique. A three-way interaction between time, technique, and gender was found for the anterior and lateral compartments and subjective per-ception of lower leg pain. The males showed statistical significance for the anterior (t(6) = 8.434, p < 0.05) and lateral (t(6) = 3.076, p < 0.05) ICPs between baseline and 1-minute post exercise when using the classic technique versus the skate technique. Although not statistically significant, the females showed higher anterior and lateral ICPs at 1-minute post exercise when using the skate technique versus the classic technique. The males` subjective perception of pain was statistically greater at 1-minute post exercise during classic rollerskiing versus skate rollerskiing, whereas the females` subjective perception of pain was statistically greater at 1-minute post exercise during skate rollerskiing versus classic rollerskiing. Conclusions: Our results suggest that Nordic skiing contributes to increases in ICPs which may lead to the development of CECS. Additonally, there may be a potential gender affect between the Nordic skiing techniques. This is the first study of its kind on Nordic skiing and CECS. These results help provide greater knowledge regarding the present phenomenon in which Nordic athletes commonly experience increases in the anterior and lateral compartments during ski activity, particularly during classic rollerskiing and skate skiing over icy snow.